Development of a capacitive sensor for spray deposition and drift measurements - Tingting Yan; Zhihong Zhang; Jingwu Shou (Smart Agricultural Technology)
Techniques to detect droplet deposition and drift is needed to achieve precision spray applications on intended targets and minimize negative environmental impact. A novel capacitive sensor for detection of droplet deposition and drift was developed to provide quick feedback information on spray quality for pesticide applications. The relationship between the capacitance change (∆C) and the droplet mass (m) was analyzed. Five different designs of the sensor with different distances between plates (d) (0.535, 0.785, 0.985, 0.335 and 0.185 mm) were used to evaluate the sensor performance in detecting spray deposition and drift for water-based droplets of different volumes (0.5, 1, 2, 3, 4, 5, 6, 7 and 8 µL) with different solutions (TW, S1, S2 and S3). Results of the indoor experiments showed that ∆C correlated with Va very well when d was small. The slopes between ∆C and Va of different solutions varied with the density and dielectric constant. The data of spray deposition detection demonstrated that R2 increased as d decreased. The proposed sensor would have great potential to provide a convenient tool for detection of droplet deposition and drift under various laboratory and field conditions, significantly improve the experimental efficiency especially for field experiments.